Growth and developmental changes of the age-group swimmer
Faster swimmers at the younger ages tend to be early maturers, while in the older age-groups they are normal or late maturers. The USA national team comprised 80% on-time, 18% late, and 2% early maturers. Faster early maturing swimmers have higher anaerobic capacities, larger muscle mass, and greater muscle power, features which are sufficient to produce success in short races (e.g., 50 or 100 m). Younger, less mature swimmers have to attempt to match their physically advanced rivals by accentuating skill. They tend to be more economical, at least in part because they have a very small anaerobic capacity. There is a distinct disadvantage to being an early maturer in younger age-group competitions. Success is achieved at the expense of skill development. Later in their careers when later-maturing individuals catch up in strength and size, the lack of skill grounding in the formative years of participation is an impediment. Training categories of work may be made individual-specific after the age of 12 but prior to that the only energy system worthy of being stimulated is the aerobic system. Endurance based training is the single most important component of training throughout the entire swimming career. Implication: The best swimming program for pre-pubertal swimmers would be one that stresses skill development and aerobic training. Competitive programs should be structured to focus on and require those elements to be emphasized. There should be a deliberate attempt to program competitive events that do not require strength and size for success. If that was achieved, early maturers would have to stress skill in their swimming, a feature that would remain beneficial throughout their swimming careers.